4CPS-380 An integrated pharmacist led medication review service for elective surgery patients at the pre-anaesthesia outpatient clinic. (14th March 2021) - Kappaun, W; Stemer, G; Baron, D; Anditsch, M
Abstract : Background and importance: Drug related problems (DRPs) (eg, untreated indication, drug–drug interactions (DDIs) and contraindicated medicines) significantly contribute to patient harm. Especially in surgical departments, DRPs often represent a significant threat to patient safety. Therefore, an integrated pharmacist led medication review service was initiated at the pre-anaesthesia outpatient clinic of a 1700 bed tertiary care centre. Aim and objectives: The aim was to evaluate the impact of medication reviews prior to elective surgery, quantitatively and qualitatively, by describing DRPs, pharmaceutical interventions and their acceptance rate. Material and methods: During the 5 month study period, patients undergoing elective surgery were prioritised by age and anaesthesia risk score, after their preoperative evaluation. Their medication regimens and further relevant data (eg, laboratory values, comorbidities) were reviewed. In the case of inconsistencies, patients were called to amend and verify their current regimens. Identified DRPs and corresponding interventions were suggested in written form to the respective surgical department. A follow-up of interventions was performed by retrospective analysis of patients' discharge letters. Results: Medication reviews were performed in 1281 patients (51% women, 64±18 years of age). A total of 1742 DRPs were identified in 700 (54, 6%) patients, accounting for an average of 2.5 DRPs per patient. The three most common DRPs, apart from the need for specific medication information (27% of patients), were potential DDIs (7.1%), non-conformity to therapeutic guidelines (5.6%) and untreated indications (5.5%). The three most common interventions were the provision of medication related information (49.7%), the recommendation of additional medicines (11.1%) and patient monitoring (10%). 52% of interventions were accepted, while a high proportion of interventions were lost to follow-up. Conclusion and relevance: The study results showed that pharmacist led medication reviews prior to surgery significantly contributed to the prevention of DRPs. Inappropriate and incomplete information in the medical record was commonly encountered as a barrier to the interventions. The moderate acceptance rate needs to be analysed further (eg, acceptance rate per intervention categories) and strategies to optimise approval of recommendations need to be discussed with different surgery departments. References and/or acknowledgements: The performance of medication reviews by all pharmacists of the clinical pharmacy department is acknowledged. Conflict of interest: No conflict of interest